Glucagon-Like Peptide-1 Receptor Imaging with [Lys40(Ahx-HYNIC-99mTc/EDDA)NH2]-Exendin-4 for the Diagnosis of Recurrence or Dissemination of Medullary Thyroid Cancer: A Preliminary Report. (31st March 2013) - Pach, D.; Sowa-Staszczak, A.; Jabrocka-Hybel, A.; Stefańska, A.; Tomaszuk, M.; Mikołajczak, R.; Janota, B.; Trofimiuk-Müldner, M.; Przybylik-Mazurek, E.; Hubalewska-Dydejczyk, A.
Abstract : Introduction . Epidemiological studies on medullary thyroid cancer (MTC) have shown that neither a change in stage at diagnosis nor improvement in survival has occurred during the past 30 years. In patients with detectable serum calcitonin and no clinically apparent disease, a careful search for local recurrence, and nodal or distant metastases, should be performed. Conventional imaging modalities will not show any disease until basal serum calcitonin is at least 150 pg/mL. The objective of the study was to present the first experience with labelled glucagon-like peptide-1 (GLP-1) analogue [Lys 40 (Ahx-HYNIC- 99m Tc/EDDA)NH2 ]-exendin-4 in the visualisation of MTC in humans. Material and Method . Four patients aged 22–74 years (two with sporadic and two with MEN2 syndrome-related disseminated MTC) were enrolled in the study. In all patients, GLP-1 receptor imaging was performed. Results . High-quality images were obtained in all patients. All previously known MTC lesions have been confirmed in GLP-1 scintigraphy. Moreover, one additional liver lesion was detected in sporadic MTC male patient. Conclusions . GLP-1 receptor imaging with [Lys 40 (Ahx-HYNIC- 99m Tc/EDDA)NH2 ]-exendin-4 is able to detect MTC lesions. GLP-1 scintigraphy can serve as a confirmatory test in MTC patients, in whom other imaging procedures are inconsistent.